STUDENTS’ EXPECTATIONS ON THE IMPLEMENTATION OF MERDEKA CURRICULUM - MUTIA SAFRIYANTINUR (Merwin Publisher, 2025)
The curriculum is used as a regulation to develop a well-organized educational system to prepare for advanced civilization. This research aimed to investigate the students’ expectations on the implementation of merdeka curriculum in grade X SMA Negeri 1 Pangkalan Susu 2024/2025. The subjects of the research were 36 students. It is a qualitative research design that the data was collected by a questionnaire that used a Likert scale to analyze the data. Having analyzed the data, it is found that students have some expectations on the implementation of Kurikulum Merdeka, they are: (1) Kurikulum Merdeka is expected to be better prepare students for the future job market; (2) Kurikulum Merdeka is expected to reduce the academic burden and stress on students; (3) Kurikulum Merdeka is expected to help students develop a strong sense of identity and character; (4) Kurikulum Merdeka is expected to provide more opportunities for students to develop the talented they have; (5) Merdeka Curriculum is expected to provide a joyful learning that motivates them maximally; (6) Merdeka Curriculum is expected to help students achieve their full potential. However, the students expectation of merdeka curriclum hopefully can be revealed through a well-organized implementation of merdeka curriculum.